If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 144 = x(x + 2) * 3 Reorder the terms: 144 = x(2 + x) * 3 Reorder the terms for easier multiplication: 144 = 3x(2 + x) 144 = (2 * 3x + x * 3x) 144 = (6x + 3x2) Solving 144 = 6x + 3x2 Solving for variable 'x'. Reorder the terms: 144 + -6x + -3x2 = 6x + -6x + 3x2 + -3x2 Combine like terms: 6x + -6x = 0 144 + -6x + -3x2 = 0 + 3x2 + -3x2 144 + -6x + -3x2 = 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 144 + -6x + -3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(48 + -2x + -1x2) = 0 Factor a trinomial. 3((6 + -1x)(8 + x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Subproblem 2
Set the factor '(8 + x)' equal to zero and attempt to solve: Simplifying 8 + x = 0 Solving 8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + x = 0 + -8 x = 0 + -8 Combine like terms: 0 + -8 = -8 x = -8 Simplifying x = -8Solution
x = {6, -8}
| (6-5n)(6+5n)= | | 5*(2b-14)=5*b+1 | | 4b^2-8b=0 | | 6i^28=6 | | 2*m+11=4*m*11 | | 85x+1.10x=280 | | 6i^28=i | | 15x+5(.75x)=90 | | 6i^28=x | | 85x+280+1.10x=0 | | 8x^3+6x^2+x=0 | | (1b-8)(5b-2)= | | 15x+5y=90 | | (B-8)(5b-2)= | | 7(9x)+4= | | (x^2-25)= | | 3x-7=48-12x | | (6a-3)(4a-1)= | | x^2-12x+36=18 | | w-2=0 | | x^2+5x-3=3 | | 15a+8b-4a-b= | | 3-2t+1=12 | | 5t^2-7t-1=0 | | 1+5t+5=16 | | 5t^2-7+1=0 | | 15x+7=-19+2x | | 2e-12=7e+15 | | 3x+6y=20 | | 0.5(0.5x)(x)=196 | | 1-5t+5=16 | | 4z^4+2z^3-4z=0 |